2010
DOI: 10.1177/1932202x1002100205
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Grade Span Configuration and Academic Achievement

Abstract: Dove, M. J., Pearson, L. C., & Hooper, H. (2010). Relationship between grade span configuration and academic achievement. Journal of Advanced Academics, 21, 272-298.In an effort to address the NCLB-mandated testing process, one of the issues to be considered is how best to configure student populations to maximize all aspects of the educational setting while simultaneously maximizing student achievement; one aspect is grade span configuration. We examined the relationship between the grade span configuration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Similarly, Poncelet and Metis Associates (2004) found that sixth graders in Kindergarten through eighth-grade schools in Cleveland city demonstrated greater mathematics and reading achievement than students in sixth-through eighth-grade schools. In contrast, Dove, Pearson, and Hooper (2010) found no relationship between grade configuration and mathematics or literacy scores for sixth-grade students in Arkansas middle schools.…”
Section: Sixth-and Seventh-grade Studiesmentioning
confidence: 61%
“…Similarly, Poncelet and Metis Associates (2004) found that sixth graders in Kindergarten through eighth-grade schools in Cleveland city demonstrated greater mathematics and reading achievement than students in sixth-through eighth-grade schools. In contrast, Dove, Pearson, and Hooper (2010) found no relationship between grade configuration and mathematics or literacy scores for sixth-grade students in Arkansas middle schools.…”
Section: Sixth-and Seventh-grade Studiesmentioning
confidence: 61%
“…One-room, ungraded schools merged into larger schools, introducing the graded system in the mid-1800's, and grades one through eight were usually the norm (Dove, Hooper, & Pearson, 2010). The evolution of grade configurations from this one room schoolhouse model has been hastened by several factors including economics, content development, and growing knowledge of the varied instructional and developmental needs of students.…”
Section: The Evolution Of Gradesmentioning
confidence: 99%
“…Our traditional structure of primary-secondary school is based in 19 th Century economics where the goal was to transition students into the workforce (Hough, 1995). Dove, et al (2010), contend that the change from an agricultural society to an industrial society hastened the need for more education in order to secure better employment. The goals of education were keeping pace with economic changes, and these circumstances became the primary catalysts for changes in grade spans.…”
Section: The Evolution Of Gradesmentioning
confidence: 99%